2003
DOI: 10.1046/j.1538-7836.2003.00108.x
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced monocyte expression of tissue factor by oxidative stress in patients with antiphospholipid antibodies: effect of antioxidant treatment

Abstract: Summary. In a first study, we performed a cross-sectional analysis of urinary excretion of isoprostanes, IPF 2a-III and VI , and monocyte tissue factor (TF) antigen and activity between 11 antiphospholipid (APL) antibody-positive patients and 13 APL negative subjects. In a second study, 11 APL positive patients were randomly supplemented either with (n ¼ 6) or without (n ¼ 5) antioxidants (vitamin E at 900 IU day À1 , vitamin C at 2000 mg day À1 ) for 6 weeks. In a third study, TF and superoxide anion were mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
28
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 31 publications
5
28
0
Order By: Relevance
“…It is well accepted that aPL promote thrombosis by interfering with normal cell surface haemostatic mechanisms and by inducing proinflammatory and procoagulant cellular phenotypes tissue factor by aPL in endothelial cells and monocytes (Ferro et al 2003;Giannakopoulos et al 2007). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well accepted that aPL promote thrombosis by interfering with normal cell surface haemostatic mechanisms and by inducing proinflammatory and procoagulant cellular phenotypes tissue factor by aPL in endothelial cells and monocytes (Ferro et al 2003;Giannakopoulos et al 2007). …”
Section: Discussionmentioning
confidence: 99%
“…The aPL are a very heterogeneous group of autoantibodies with an antigen specificity that still remains elusive, although their binding to different negatively charged phospholipids such as cardiolipin and phosphatidylserine and to protein binding cofactors like b-2-glycoprotein I (b2GPI) (Shoenfeld 2003) is well known. One of the mechanisms proposed for aPL is the stimulation of tissue factor (TF) expression in endothelial cells and monocytes (Roubey 2000;Ferro et al 2003;Kornberg et al 1994). TF as the main initiator of the coagulation cascade could therefore be one of the strongest triggers of thrombosis in the pathophysiology of APS (Lopez-Pedrera et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, studies in patients with antiphospholipid syndrome, which promotes a hypercoagulable state, have demonstrated that coagulation is activated by oxidative stress via overexpression of monocyte tissue factor (Ferro et al . ). Without the analysis of PF1+2 and T‐AT, these data would suggest increased coagulation activation and support the hypoxic findings of Wang and colleagues (2009).…”
Section: Discussionmentioning
confidence: 97%
“…[21] It has been observed that enhanced TF expression on the monocytes in response to activated platelets during oxidative stress condition, followed by supplementation of antioxidants significantly decreased monocytes TF antigen and its activity. [22] 6,7-dimethoxycoumarin has already been proven that it has the capability of reducing superoxide anion-mediated TF expression and avert disseminated intravascular coagulation. [19] It is clear from our study that 6,7-dimethoxycoumarin significantly reduced aCL antibody-mediated TF overexpression in placenta, and increased the platelet count to be comparable with negative control mice (normal level).…”
Section: Discussionmentioning
confidence: 99%